Barriers and facilitators to the implementation of clinical practice guidelines: A cross-sectional survey among physicians in Estonia - Taba Pille; Rosenthal Marika; Habicht Jarno; Tarien Helvi; Mathiesen Mari; Hill Suzanne; Bero Lisa (BMC, 2012)
Abstract Background In an era when an increasing amount of clinical information is available to health care professionals, the effective implementation of clinical practice guidelines requires the development of strategies to facilitate the use of these guidelines. The objective of this study was to assess attitudes towards clinical practice guidelines, as well as the barriers and facilitators to their use, among Estonian physicians. The study was conducted to inform the revision of the clinical practice guideline development process and can provide inspiration to other countries considering the increasing use of evidence-based medicine. Methods We conducted an online survey of physicians to assess resource, system, and attitudinal barriers. We also asked a set of questions related to improving the use of clinical practice guidelines and collected free-text comments. We hypothesized that attitudes concerning guidelines may differ by gender, years of experience and practice setting. The study population consisted of physicians from the database of the Department of Continuing Medical Education of the University of Tartu. Differences between groups were analyzed using the Kruskal-Wallis non-parametric test. Results 41% (497/1212) of physicians in the database completed the questionnaire, comprising more than 10% of physicians in the country. Most respondents (79%) used treatment guidelines in their daily clinical practice. Lack of time was the barrier identified by the most physicians (42%), followed by lack of medical resources for implementation (32%). The majority of physicians disagreed with the statement that guidelines were not accessible (73%) or too complicated (70%). Physicians practicing in outpatient settings or for more than 25 years were the most likely to experience difficulties in guideline use. 95% of respondents agreed that an easy-to-find online database of guidelines would facilitate use. Conclusions Use of updated evidence-based guidelines is a prerequisite for the high-quality management of diseases, and recognizing the factors that affect guideline compliance makes it possible to work towards improving guideline adherence in clinical practice. In our study, physicians with long-term clinical experience and doctors in outpatient settings perceived more barriers, which should be taken into account when planning strategies in improving the use of guidelines. Informed by the results of the survey, leading health authorities are making an effort to develop specially designed interventions to implement clinical practice guidelines, including an easily accessible online database.